1996
DOI: 10.1172/jci118990
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to nuclear envelope antigens in chronic fatigue syndrome.

Abstract: We have identified and partially characterized the autoantibodies in sera of 60 patients with chronic fatigue syndrome. Approximately 52% of the sera were found to react with nuclear envelope antigens. The combination of nuclear rim staining observed in immunofluorescence microscopy and immunoblot analysis of highly purified nuclear envelope proteins provided initial characterization of these autoantibodies. Further characterization showed that some sera immunoprecipitated the in vitro transcription and transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
2
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 34 publications
0
60
2
1
Order By: Relevance
“…A third study found no difference in the percentage of patients showing these abnormalities relative to controls (40) (v) Antinuclear antibodies. A number of papers have reported that CFS patients have a higher rate of autoantibody positivity than controls (3,27,48). However, a follow-up report using data from a number of CFS centers did not find similar differences between patients and controls (M. Sugiura, D. Daniels, D. Buchwald, A. Komaroff, M. Hossein, M. Peakman, S. Wessely, B. Natelson, I. Hay, P. Levine, and E. M. Tan, Abstr.…”
Section: Inconsistent Immune Markersmentioning
confidence: 99%
“…A third study found no difference in the percentage of patients showing these abnormalities relative to controls (40) (v) Antinuclear antibodies. A number of papers have reported that CFS patients have a higher rate of autoantibody positivity than controls (3,27,48). However, a follow-up report using data from a number of CFS centers did not find similar differences between patients and controls (M. Sugiura, D. Daniels, D. Buchwald, A. Komaroff, M. Hossein, M. Peakman, S. Wessely, B. Natelson, I. Hay, P. Levine, and E. M. Tan, Abstr.…”
Section: Inconsistent Immune Markersmentioning
confidence: 99%
“…The 27 proteins identified could be assigned to one of the following three groups. (i) Proteins already defined as TAAs such as grp78 [4], or proteins associated with autoaggressive immunity such as AH-NAK nucleoprotein [5], vimentin [6], and hsc70 [7]. (ii) Proteins of known function, which had not been associated with cancer (tropomyosin alpha, elongin A2).…”
Section: Resultsmentioning
confidence: 99%
“…Combination of nuclear rim staining observed in indirect immunofluorescence microscopy and immunoblot analysis of highly purified proteins provided initial characterization of these autoantibodies. The occurrence of autoantibodies to a conserved intracellular protein, such as lamin B1, provided new laboratory evidence for an autoimmune component in chronic fatigue syndrome [Konstantinov et al, 1996;von Mikecz et al, 1997, reviewed in Bennet, 1998]. In addition, between 10 and 42% of patients with primary biliary cirrhosis have been reported to have antibodies against gp210, a glycoprotein of the nuclear pore complex (NPC) [Wesierska-Gadek et al, 1995;Bandin et al, 1996;Courvalin and Worman, 1997].…”
Section: Nuclear Envelopementioning
confidence: 99%